Estimates of historical exposures by phase contrast and transmission electron microscopy in North Carolina USA asbestos textile plants. Issue 9 (19th September 2008) - Dement, J M; Myers, D; Loomis, D; Richardson, D; Wolf, S
Abstract : Objectives: To develop a job-exposure matrix (JEM) for fibre exposures in three asbestos textile plants and to develop estimates of fibre size-specific exposures. Methods: Historical dust samples from three North Carolina, USA asbestos textile plants were obtained. Plant specific samples were used to express impinger dust concentrations as fibre concentrations by phase contract microscopy (PCM). Mixed models were used to estimate PCM exposures by plant, department, job and calendar time. Archived membrane filter samples were analysed by transmission electron microscopy (TEM) to determine the bivariate diameter/length distribution of airborne fibres by plant and operation. Results: PCM fibre levels estimated from the models were very high in the 1930s, with some operations having in excess of 200 fibres/ml, and decreased appreciably over time. TEM results for 77 airborne dust samples found that only a small proportion of airborne fibres were measured by PCM (>0.25 μm in diameter and >5 μm in length) and the proportion varied considerably by plant and operation (range 2.9% to 10.0%). The bivariate diameter/length distribution of airborne fibres demonstrated a relatively high degree of variability by plant and operation. PCM adjustment factors also varied substantially across plants and operations. Conclusions: These data provide new information concerning airborne fibre levels and characteristics in three historically important asbestos textile plants. PCM concentrations were high in the early years and TEM data demonstrate that the vast majority of airborne fibres inhaled by the workers were shorter than 5 μm in length, and thus not included in the PCM-based fibre counts.